2006
DOI: 10.1002/ijc.22056
|View full text |Cite
|
Sign up to set email alerts
|

H‐Ras selectively up‐regulates MMP‐9 and COX‐2 through activation of ERK1/2 and NF‐κB: An implication for invasive phenotype in rat liver epithelial cells

Abstract: One of the most frequent events in carcinogenesis is uncontrolled activation of Ras signaling pathway. A previous study demonstrated that the introduction of H-Ras into the normal WB-F344 rat liver epithelial (WB) cell line and adult male F344 rats resulted in tumorigenicity. The present study investigated whether H-Ras induced the invasive and migrative phenotypes in WB cells, and subsequently aimed at characterizing the underlying mechanisms. H-Ras induced the invasive and migrative phenotypes of WB cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…MMPs, such as MMP-2 and MMP-9, display strong activity in tumor cells transformed by Ras [27][28][29]. Contrary to our results, inhibition of Ras by a farnesyltransferase inhibitor reduced levels of secreted MMP-2 and MMP-9 in prostate cancer cells [30].…”
Section: Discussioncontrasting
confidence: 85%
“…MMPs, such as MMP-2 and MMP-9, display strong activity in tumor cells transformed by Ras [27][28][29]. Contrary to our results, inhibition of Ras by a farnesyltransferase inhibitor reduced levels of secreted MMP-2 and MMP-9 in prostate cancer cells [30].…”
Section: Discussioncontrasting
confidence: 85%
“…MCT-1 overexpression itself may be not only directly oncogenic but could also induce a constellation of invasive and metastatic factors (e.g., HIF-1α, MMP-9, and integrin β4) by its transcriptional or translational regulation function. The enhancing H-Ras gene expression followed by an extremely active Ras-MEK-MAPK signaling cascade reinforces tumorigenic outcomes and angiogenic effects (18,19,32). Oncogenic MCT-1 participates in stimulating the Ras-MEK-MAPK cascade ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have indicated that activation of MAPK signaling is important for cell transformation and genomic destabilization, which are induced by many oncoproteins, including Mos, Ras, and Raf (15)(16)(17). Furthermore, activating MAPK (ERK1/2) and H-Ras selectively induces cell invasive phenotypes by enhancing matrix metalloproteinase-9 (MMP-9) and cyclooxygenase-2 expression along with increasing invasion and migration abilities (18,19). The chromosome instability caused by p53 deficiency can be enhanced to a greater extent by the constitutively active MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RAS (Moon et al, 2004;Lee et al, 2006) and Rho proteins (Turner et al, 2005) are related to MMP-9 expression. Accordingly, we investigated whether simvastatin could suppress CSE-mediated MMP-9 induction via the inhibition of protein prenylation.…”
Section: Simvastatin Inhibits Mmp-9 Induction Through Protein Prenylamentioning
confidence: 99%